2022
DOI: 10.1002/btm2.10425
|View full text |Cite
|
Sign up to set email alerts
|

Pitstop‐2 and its novel derivative RVD‐127 disrupt global cell dynamics and nuclear pores integrity by direct interaction with small GTPases

Abstract: Clathrin‐mediated endocytosis (CME) is an essential cell physiological process of broad biomedical relevance. Since the recent introduction of Pitstop‐2 as a potent CME inhibitor, we and others have reported on substantial clathrin‐independent inhibitory effects. Herein, we developed and experimentally validated a novel fluorescent derivative of Pitstop‐2, termed RVD‐127, to clarify Pitstop‐2 diverse effects. Using RVD‐127, we were able to trace additional protein targets of Pitstop‐2. Besides inhibiting CME, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The binding affinities to Nups are slightly lower or almost equal to its inhibitory binding at the 𝛽propeller fold of the heavy chain of clathrin, and we, therefore, assume that Pitstop-2 may interfere simultaneously with both CME and NPCs, as concluded in our recent studies. [28,29] Substances capable of reducing the stringency of nucleocytoplasmic permeability barriers could facilitate the development of non-viral systems of intranuclear transgene delivery. [35] By causing a massive rearrangement of the NPC scaffold, Pitstop-2 can compromise the barrier's integrity without dissociating the barrier-forming nucleoporins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding affinities to Nups are slightly lower or almost equal to its inhibitory binding at the 𝛽propeller fold of the heavy chain of clathrin, and we, therefore, assume that Pitstop-2 may interfere simultaneously with both CME and NPCs, as concluded in our recent studies. [28,29] Substances capable of reducing the stringency of nucleocytoplasmic permeability barriers could facilitate the development of non-viral systems of intranuclear transgene delivery. [35] By causing a massive rearrangement of the NPC scaffold, Pitstop-2 can compromise the barrier's integrity without dissociating the barrier-forming nucleoporins.…”
Section: Discussionmentioning
confidence: 99%
“…to modulate the barrier and the active nucleocytoplasmic transport functions of the NPCs. [28,29] We reasoned that such similarity might be sufficient for the inhibitor to bind to those Nups and disrupt the structural organization of the NPC scaffold. Our hypothesis was validated by ultrastructural atomic force microscopy (AFM) imaging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we showed how nanopipettes can deform a cell via intrinsic force between the nanopipette tip and cell surface [14,15], allowing us to estimate the Young's modulus with higher resolution and with less force applied to living cells. We demonstrated that SICM for a Young's modulus estimate enables qualitative and quantitative characterization of the cytoskeleton state during alteration of cytoskeletal proteins such as F-actin and tubulin [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, using correlative confocal imaging of the cytoskeleton, we showed that the estimated Young's modulus is directly related to the state of the cytoskeleton. The developed technique was then successfully used to characterize the cytoskeleton state under different conditions [13][14][15].…”
Section: Introductionmentioning
confidence: 99%